(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Studies of risk perception, in relation to the governance of risk events, have advanced towards a management, production and knowledge transfer system focused on the impact of the media on audiences and eventually on the leaders of Civil protection institutions, but the absence of research encouraged the present work to establish the reliability and validity of an instrument. The proposal was based on a non-experimental study and a non-probabilistic sample selection of 100 students from a public university. Based on a structural model, it was found that Internet users perceive risks and affect media perception and perception social on the perception of risk events, although there are lines of research concerning the mediation of such dependency relaionships.